The problem of the obligation of a child athlete to comply with the provisions of the anti-doping legislation of Ukraine - Tikhonova, Mariia; Bermudes, Diana; Kyselov, Valerii; Maksymenko, Lyudmila; Fetko, Yuliia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Individuals of the sports school can be children and young people who have no medical contraindications for sports. Once the athlete gets enrolled in a sports school after successfully completing the required documentation process, a written letter is provided by the director of the school. Followed by this, the child acquires the corresponding status and, from that moment, he or she has a number of rights and responsibilities. Most of the sports schools prohibit the substance abuse once youth or children become part of their organization. After getting enrolled in a sports school, a child has certain responsibilities, including the obligation not to use prohibited substances and methods. In this article, the authors examine the legality of imposing this obligation on a child. The authors concluded that the child is obliged to comply with the anti-doping rules of sports organizations, but at the same time he/she has no right to buy medicines and choose a doctor on his/her own, and these things must be done by parents according to the legislation of Ukraine.